Exploring the Experiences in Developing Character Education through E-Learning During the COVID-19 Pandemic - Edy Herianto; A. Hari Witono; Muhamad Mustari; Lalu Sumardi (RIRAI Publisher, 2023)
The limited implementation of direct learning has forced lecturers and students to seek alternative learning solutions. E-learning has proven to be a suitable solution for optimal learning in this new era of education. Therefore, this qualitative phenomenology study aimed to explore the experiences of e-learning during the COVID-19 pandemic by analyzing two lecturers and 190 PK course students. Appropriate techniques and instruments were used to obtain data, and triangulation was performed to ensure its reliability. Furthermore, data analysis involved reduction, presentation, and conclusion. The results showed that (1) e-learning was implemented through various platforms such as WhatsApp Group for communication, Google Classroom for assignments and exams, and Zoom Meeting for virtual classes, (2) good learning outcomes were achieved through the use of various platforms and students’ involvement, and (3) the biggest challenge faced was the availability of electricity and internet access. The novelty of e-learning lies in its integration of different platforms with student-centered and self-directed activities.